A chopping voltage reference without low-pass filter - Rizky Wirawan Pratama (2015)
In some bandgap voltage references, an operational amplifier is included in the design to stabilize the voltage of some points in the circuit towards abnormalities. However, the usage of opamp in the circuit will cause some non-idealities, such as 1/f noise and DC offset. To remove these non-idealities, chopper stabilization technique will be introduced. Input signal to the opamp will be modulated at frequency above 1/f noise frequency and the output of the opamp will be demodulated back with additional low pass filter with large time constant. This project aims to investigate the circuit architecture which leads to low pass filterless design with UMC 65nm process.